The System of Cartographic Works for Representing the State and Development of Ukraine’s Nature Reserve Fund - Kyryliuk, M. O. (Ukrainian Geographical Journal, 2025)
The purpose of the study is to substantiate the system of cartographic works of the Nature Reserve Fund of Ukraine. The article offers an author’s approach to justifying the system of cartographic works for displaying the state and development of the NRF of Ukraine. The main cartographic works of different territorial levels dedicated to the National Reserve Fund of Ukraine, as well as the available experience and theoretical approaches to the formation of the system of cartographic works of the National Reserve Fund of Ukraine, were analyzed. Maps of protected areas should have internal unity through the unification of legends and conventional designations adapted for use using automated map creation and reading, coordination of mathematical and cartographic foundations, and unified approaches to generalization of map content based on a unified system of mapping indicators. According to the existing achievements, the system of indicators, mapping units, and methods of cartographic representation, which are expedient to use for mapping the NRF of Ukraine at different territorial levels, are substantiated. It has been analyzed that one of the possible solutions for the practical implementation of the system of cartographic works (one of the main links of this system) can be the interactive atlas of the NFR of Ukraine as a comprehensive cartographic work of the national level with a unified approach to the selection of indicators, scales of territories and objects of the NRF. Based on the maps it contains, it obtains a reliable, processed, and scientifically presented report on the state of the NRF.